2021
DOI: 10.3390/polym13234068
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Development of a Strategy to Characterize and Model the Rheological Behavior of Filled, Uncured Rubber Compounds

Abstract: In this paper, an experimental strategy is presented to characterize the rheological behavior of filled, uncured rubber compounds. Oscillatory shear experiments on a regular plate-plate rheometer are combined with a phenomenological thixotropy model to obtain model parameters that can be used to describe the steady shear behavior. We compare rate- and stress-controlled kinetic equations for a structure parameter that determines the deformation history-dependent spectrum and, thus, the dynamic thixotropic behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…When the material is deformed, these bonds can break, but after flow cessation, these bonds can reform again. To model this thixotropic behavior, a structure parameter ξ is defined which indicates the degree of structure in the material, as discussed in Spanjaards et al [23]. If ξ = 1, the material is undamaged and the filler-filler/polymer-filler networks are intact.…”
Section: Thixotropy Modelmentioning
confidence: 99%
“…When the material is deformed, these bonds can break, but after flow cessation, these bonds can reform again. To model this thixotropic behavior, a structure parameter ξ is defined which indicates the degree of structure in the material, as discussed in Spanjaards et al [23]. If ξ = 1, the material is undamaged and the filler-filler/polymer-filler networks are intact.…”
Section: Thixotropy Modelmentioning
confidence: 99%
“…A fluctuation in the output of an extrusion process is undesired, since this results in inconsistent dimensions of the extrudate. Fluctuating output is especially unfavorable when one attempts to design a die shape at certain processing conditions to optimize the extrudate dimensions for rheologically complex materials [8][9][10]. It is observed that the shape of this output fluctuation is strongly dependent on the chosen minimum gap between the gears.…”
Section: Introductionmentioning
confidence: 99%